Trauma Studies in Amber Smith’s The Way I Used To Be - Putri, Ira Atika (English Literature Study Program, 2022)
This study aimed to find out what events caused Eden's trauma and the way Eden overcame her trauma in the novel The Way I Used to Be written by Amber Smith. This research was included in the category of literary criticism that used Sigmund Freud's psychoanalysis as its research approach and Sigmund Freud's trauma theory to analyse the data. The source of data in this research was the novel written by Amber Smith entitled The Way I Used To Be. The research results revealed that the cause of trauma experienced by Eden was sexual abuse by Kevin. Apart from that, other components supported the increasing sense of trauma experienced by Eden. In this research, Eden's ways to overcome the trauma she experienced were also found, which included being honest about something happened to her, overcoming her feelings of guilt and shame, getting ready for disappointing flashbacks and memories reconnecting to her body and feelings, staying connected with her friends, and taking care of herself. Based on this research, the novel entitled The Way I Used To Be by Amber Smith could be used to illustrate how to deal with trauma. For this reason, readers could use this novel as research material with topics other than trauma issues, such as how Eden's personality changed after recovering from her trauma of sexual abuse.